McCollum and Prebluda test for vitamin B1 and its preparations - Manalo, Gloria D. 1917-
The purpose of the research is to study the application of McCollum and Prebluda test for vitamin B1 to a variety of materials containing vitamin B1 mainly the pharmaceutical preparations. Procedure: A thorough study of the McCollum and Prebluda test was made and compared it with the other known chemical tests for vitamin B1. Methods were devised for the application of the test to tiki-tiki, extract of tikitiki, Pharmaceutical preparations containing crystalline vitamin B1 hydrochloride, yeast preparations, fruits and vegetables and other food materials. A study was also made on the quantitative application of the test on tikitiki and extract of tikitiki. Approximate amount of time devoted to research is about 16 months. DEGREE OF SUPERVISION: The candidate was given sufficient opportunity to work independently and develop initiative in research. Occasional consultations and conferences between the candidate and the adviser on one hand and the candidate and the graduate seminar on the other, were held. SUCCESS OF THE INVESTIGATION: The application of the test for tikitiki and extract of tikitiki was extensively and successfully made. For the first time, the test was applied to a variety of vitamin B1 containing materials in accordance with the procedure originally devised by the candidate. The study of the test for the quantitative determination of vitamin B1 augurs well for a rapid chemical quantitative estimation of vitamin B1 in a solution or food material, which offers greater advantages over the biological methods used.
Available to the general public.
Thesis (Master of Science in Pharmacy)--University of the Philippines, 1939.
Keywords: Vitamin B1 -- Chemical analysis